2013
DOI: 10.1080/15248372.2012.698434
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Actions and Emotions in Deaf Children: Evidence From a Biological Motion Task

Abstract: This study aimed to explore the recognition of emotional and non-emotional biological movements in children with severe and profound deafness. 24 deaf children, together with 24 control children matched on mental age and 24 control children matched on chronological age, were asked to identify a person's actions, subjective states, emotions, and objects conveyed by moving point-light displays. Results showed that when observing point light displays, deaf children showed impairments across all conditions (emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…They found that children with severe hearing impairment could recognize and understand emotions in 85% and 95% cases. Somewhat different results were reached byLudlow, et al (2012), it was found that deaf children achieved lower results in most experimental cases, that is they identified fewer emotions while watching movie compared to hearing children Sidera, et al (2017). state that there is a deficit in recognition skills of specific emotions (i.e., fear, sadness, disgust) in children with hearing impairments.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…They found that children with severe hearing impairment could recognize and understand emotions in 85% and 95% cases. Somewhat different results were reached byLudlow, et al (2012), it was found that deaf children achieved lower results in most experimental cases, that is they identified fewer emotions while watching movie compared to hearing children Sidera, et al (2017). state that there is a deficit in recognition skills of specific emotions (i.e., fear, sadness, disgust) in children with hearing impairments.…”
mentioning
confidence: 90%
“…10.51558/2744-1555.2023.6.1.95 105 Also results of previous studies often showed that deaf children have impaired emotional competence, but they also tend to recognize negative emotions faster than their hearing pears, because negative facial expressions signal danger to deaf people which is related to the fact that they are visual types.CONCLUSIONRecognition of other people's emotions is an important part of everyday communication and in social adaptation and personal development likewise. The ability to recognize emotions is an important component of nonverbal communication systems.…”
mentioning
confidence: 99%